2018
DOI: 10.1002/14651858.cd012289.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Systemic corticosteroids for acute otitis media in children

Abstract: The evidence for the effect of systemic corticosteroids on AOM is of low to very low quality, meaning the effect of systemic corticosteroids on important clinical outcomes in AOM remains uncertain. Large, high-quality studies are required to resolve the question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, their use should be considered in severe or complicated cases. Some authors suggest that the combined use of steroids and antibiotics improve the resolution of middle ear exudates when compared with antibiotics alone [23]. A systematic review by Ranakusuma et al evidenced an overall improvement in symptoms and a faster resolution of the middle ear inflammation in children treated with systemic steroids [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, their use should be considered in severe or complicated cases. Some authors suggest that the combined use of steroids and antibiotics improve the resolution of middle ear exudates when compared with antibiotics alone [23]. A systematic review by Ranakusuma et al evidenced an overall improvement in symptoms and a faster resolution of the middle ear inflammation in children treated with systemic steroids [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is insufficient evidence of efficacy and harms for AOM. A Cochrane review of randomised controlled trials (RCTs) of corticosteroids for AOM (two small studies; very low to low quality) indicated it might be useful clinically, but the small sample size and wide confidence intervals around the observed results leave too much uncertainty [ 20 ]. An additional RCT of corticosteroids showed a reduction of the duration of ear discharge in children with AOM and ventilation tubes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%